Frequency of Blood Groups in Patients with Diabetes Mellitus - Yasmine Abu Shaala,; Amal Asweb, (AlQalam Journal of Medical and Applied Sciences, 2024)
Diabetes Mellitus (DM) is a metabolic disorder which is characterized by a defect in insulin secretion leading to disturbances of carbohydrate and fat metabolism and resulting in hyperglycemia. It is classified as insulin dependent DM (type 1 DM) and non-insulin dependent DM (type-2 DM). The relationship between DM and ABO/Rhesus blood groups is still controversial. The aim of this study was to determine the relationship between ABO/Rhesus blood groups with type-1 and type-2 DM. The study included cases visiting of the specialized center for the regulation and treatment of diabetes and endocrine diseases Misrata, during two years, from the beginning of 1 January 2021 to 31 December 2022, with type 1and type diabetes of both sexes, with the exclusion of patients who did not meet the data. Among the data collected were age, sex, type of diabetes, blood groups. The study included 893 diabetic patients during the aforementioned period, where the percentage of men was 56%, while females were 44%, and the percentage of type 1 diabetes was 10.6%, while type 2 was 89.4%, and the ages ranged between 16-85 years, and there was no association between diabetes and type blood group with no significant differences were p-value = 0.258. There was no association between diabetes and blood type blood with no significant differences. داء السكري هو اضطراب أيضي يتميز بخلل في إفراز الأنسولين يؤدي إلى اضطرابات في التمثيل الغذائي للكربوهيدرات والدهون وينتج عنه ارتفاع سكر الدم. يصنف على أنه داء السكري المعتمد على الأنسولين (داء السكري من النوع الأول) وداء السكري غير المعتمد على الأنسولين (داء السكري من النوع الثاني). لا تزال العلاقة بين داء السكري وفصائل الدم ABO / Rhesus مثيرة للجدل. كان الهدف من هذه الدراسة تحديد العلاقة بين فصائل الدم ABO / Rhesus مع داء السكري من النوع الأول والثاني. شملت الدراسة حالات زارت المركز المتخصص لتنظيم وعلاج مرض السكري وأمراض الغدد الصماء مصراتة، خلال عامين، من بداية 1 يناير 2021 إلى 31 ديسمبر 2022، مع مرضى السكري من النوع الأول والنوع الثاني من كلا الجنسين، مع استبعاد المرضى الذين لم تنطبق عليهم البيانات. ومن بين البيانات التي تم جمعها العمر والجنس ونوع السكري وفصائل الدم. شملت الدراسة 893 مريض سكري خلال الفترة المذكورة، حيث بلغت نسبة الذكور 56%، بينما كانت نسبة الإناث 44%، وكانت نسبة مرضى السكري من النوع الأول 10.6%، بينما كان النوع الثاني 89.4%، وتراوحت الأعمار بين 16-85 سنة، ولم يكن هناك ارتباط بين مرض السكري وفصيلة الدم مع عدم وجود فروق ذات دلالة إحصائية حيث كانت قيمة الاحتمال = 0.258. لم يكن هناك ارتباط بين مرض السكري وفصيلة الدم مع عدم وجود فروق ذات دلالة إحصائية